2002
DOI: 10.2139/ssrn.318899
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Programs, the Discouraged-worker Effect, and Labor Force Participation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
3
11
0
1
Order By: Relevance
“…Recent work in Lechner and Wunsch (2006), Lechner, Miquel, and Wunsch (2007), Johansson (2001), Kluve (2007), and others emphasize that the effects of active labor market programs in Europe depend on the state of the economy, typically finding a direct relationship between their effectiveness and the unemployment rate. For the United States, Hotz, Imbens, and Klerman (2006) present evidence for California pointing to an inverse relationship between the labor market programs and the unemployment rate.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in Lechner and Wunsch (2006), Lechner, Miquel, and Wunsch (2007), Johansson (2001), Kluve (2007), and others emphasize that the effects of active labor market programs in Europe depend on the state of the economy, typically finding a direct relationship between their effectiveness and the unemployment rate. For the United States, Hotz, Imbens, and Klerman (2006) present evidence for California pointing to an inverse relationship between the labor market programs and the unemployment rate.…”
Section: Introductionmentioning
confidence: 99%
“…Employment subsidies instead directly decrease labour costs for firms. ALMP participation may also have a positive effect on labour force participation, in that it increases the motivation to actively seek work and therefore increases the competition for the jobs available (Johansson, 2001).…”
Section: The Theoretical Effects Of Almpsmentioning
confidence: 99%
“…24 On the positive side, there is some evidence that ALMPs have encouraged labor force participation, which may have facilitated the employment rebound in the late 1990s. Johansson (2001) examined panel data on labor market programs and labor force participation for Swedish municipalities over the period [1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998]. She found that a rise in program 24 Calmfors et al (2001) present a comprehensive survey of Swedish experiences of active labor market policies.…”
Section: Active Labor Market Policymentioning
confidence: 99%